On Developing of Smart Home with Pervasive Approach - Kalamullah Ramli; Abdurrahman Alayderous; Muhammad Salman (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
The paper describes our study and development of smart home by taken into account the concept of pervasive technology. The system integrates pervasive concept into the design of its hardware and software architecture, functionalities and system configuration. Pervasive technology is aimed at giving users access to information sources anywhere, anytime and on -demand. Pervasive access to and from the smart home can be done simultaneously via remote control, sms, web-camera and web-based Internet connection.Keywords: Smart home, Pervasive technology